The Development of English-Speaking Skill by Using Problem-Based Learning for the First Year B.A. Students of Teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University - Sriwarapong, Thir; Tikkhavajiro, Phramaha Rungphet; Chantimachaiamorn, Chuenaarom (Journal of Asian Language Teaching and Learning (Online), 2025)
This research studied of development English-Speaking Skill by Using Problem-Based Learning for the First Year B.A. Students of Teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. The objectives were: 1) to study the needs and the problem of English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. 2) to develop the English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. 3) to study satisfaction in English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. This research has used the pre-Experimental research by using pre and post experiment. The results of this research were found that 1) the needs and problems of English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University 2) the pupils who have the score post-test of use the manual of English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. ( = 17.50, S.D. = 1.15) were higher than pre-test of the score pre-test in the of use experiment the manual of English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University. ( = 9.20, S.D. = 1.28) as statistically significant at 0.5. 3) satisfaction of use experiments the manual of English-speaking skill by using Problem-Based Learning for the First Year B.A. students of teaching English (International Program) in Education Faculty at Mahachulalongkornrajavidyalaya University was found that the overall average was 4.26 which was at satisfied level.